(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless Sensor Networks (WSN) has many applications like disaster relief operations, biodiversity mapping, medicine and health care. Recent researches show that many routing protocols are being developed that prolong the network lifetime and reduces energy consumption. Although there are many challenges in WSN only some are addressed. The main challenges to be addressed are energy consumption, Quality of Service (QoS), power management and network lifetime enhancement. To overcome these issues many efficient and effective routing protocols should be used. This paper surveys the routing design issues and routing protocols in WSNs.